2021
DOI: 10.3390/cancers13061469
|View full text |Cite
|
Sign up to set email alerts
|

The Epithelial–Mesenchymal Transcription Factor SNAI1 Represses Transcription of the Tumor Suppressor miRNA let-7 in Cancer

Abstract: We aimed to determine the mechanism of epithelial–mesenchymal transition (EMT)-induced stemness in cancer cells. Cancer relapse and metastasis are caused by rare stem-like cells within tumors. Studies of stem cell reprogramming have linked let-7 repression and acquisition of stemness with the EMT factor, SNAI1. The mechanisms for the loss of let-7 in cancer cells are incompletely understood. In four carcinoma cell lines from breast cancer, pancreatic cancer, and ovarian cancer and in ovarian cancer patient-der… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 69 publications
0
18
0
Order By: Relevance
“…The EMT transcription factor SNAI1 represses transcription of the TS miRNA Let-7 in cancer. SNAI1 bind let-7 family promoters to inhibit miRNA transcription (27).…”
Section: Ts Mirna Promote Apoptosis In Cancermentioning
confidence: 99%
“…The EMT transcription factor SNAI1 represses transcription of the TS miRNA Let-7 in cancer. SNAI1 bind let-7 family promoters to inhibit miRNA transcription (27).…”
Section: Ts Mirna Promote Apoptosis In Cancermentioning
confidence: 99%
“…Analysis of a panel of patient-derived high-grade serous ovarian cancer cells revealed an inverse association between microRNA let-7 expression and the cancer stem cell phenotype, with low let-7 levels being associated with an epithelial phenotype [ 84 ]. This finding may be associated with a regulatory impact of the EMT-marker snail on let-7 [ 85 ]. One target of let-7d is c-Myc, an essential oncogenic transcription factor that is involved in tumor pathogenesis and frequently dysregulated in cancer [ 86 ].…”
Section: Let-7d and Ovarian Cancermentioning
confidence: 99%
“…While the regulation of let-7 is incompletely understood, transcriptional, post-transcriptional, and epigenetic regulation are known to occur [ 30 ]. Factors that decrease levels of let-7 have also been shown to increase the stemness, invasiveness, and chemoresistance of cancer cells [ 31 , 32 , 33 ]. In our previous work, we demonstrated that patient-derived (PD) samples with low levels of let-7 correlate with increased self-renewal, pluripotency, and tumor burden [ 34 ].…”
Section: Introductionmentioning
confidence: 99%